The Impact of Using Monopoly Game as Learning Media to Increase Motivation on Earth and Solar System Materials - Murtiyani, Tri; Muhtaj, Mughnil; Salsabila, Nadhira Fasya; Kurnianto, Wirayoga Abdillah; Kurniawan, Yudi; Mualiyah, Siti (Vocational: Journal of Educational Technology, 2024)
Several studies had found that teachers meet difficulties in helping students understanding the concept of solar system because the lack of engagement in learning process. This study aims to increase students' learning motivation with the help of monopoly learning media. This research is Classroom Action Research (CAR) using the Kemmis & Mc Taggart model. The subjects of this study were 22 class VII-4 students at SMPN 1 Gapura. The research instrument used was a learning motivation questionnaire. The study results show that student's motivation to learn has increased after participating in learning with the help of monopoly learning media. In the pre-cycle, the average level of learning motivation was 69%; in cycle 1, it was 81%, and in cycle 2, it was 85%. The study's results also show that each Indicator's learning motivation level increases in each cycle. Therefore, the application of monopoly learning media can be an alternative to increase student learning motivation because the application of monopoly media has proven to be effective in increasing student learning motivation.